Inferring and Using Location Metadata to Personalize Web Search - Bennett, Paul; Radlinski, Filip; White, Ryen W.; Yilmaz, Emine (Proceedings of the ACM International Conference on Research and Development in Information Retrieval (SIGIR), 2011)
Personalization of search results offers the potential for significant improvements in Web search. Among the many observable user attributes, approximate user location is particularly simple for search engines to obtain and allows personalization even for a first-time Web search user. However, acting on user location information is difficult, since few Web documents include an address that can be interpreted as constraining the locations where the document is relevant. Furthermore, many Web documents – such as local news stories, lottery results, and sports team fan pages – may not correspond to physical addresses, but the location of the user still plays an important role in document relevance. In this paper, we show how to infer a more general location relevance which uses not only physical location but a more general notion of locations of interest for Web pages. We compute this information using implicit user behavioral data, characterize the most location-centric pages, and show how location information can be incorporated into Web search ranking. Our results show that a substantial fraction of Web search queries can be significantly improved by incorporating location-based features.